Circulating immune complexes in subacute infective endocarditis and post-streptococcal glomerulonephritis. Issue 4 (April 1977) - Mohammed, I; Ansell, B M; Holborow, E J; Bryceson, A D
Abstract : Two out of five patients with subacute infective endocarditis and two patients with post-streptococcal glomerulonephritis had large amounts of soluble circulating immune complexes in their sera. The three others with endocarditis had less severe disease and minimal evidence of circulating immune complexes. Low serum complement was also found in two of the cases.